The effect of solar cells distribution on the Performance of solar panel - Baghdad Science Journal (مجلة بغداد للعلوم, 2010)
Three different distribution modules of silicon solar cells in a panel are used in this study . Each module consists of five identical circular silicon solar cells of radius (5cm) and then the total panel areas are identical. The five solar cells are arranged in the panel in different shapes: circular, triangular and rectangular .The efficiency for these three panel distribution are measured indoor and outdoor. The results show that the efficiency is a function of the cells distribution.